2019
DOI: 10.21061/jvs.v5i1.111
|View full text |Cite
|
Sign up to set email alerts
|

Protective Factors for Suicide: A Multi-Tiered Veteran-Driven Community Engagement Project

Abstract: Background There are approximately 20 million veterans living in the United States today (U.S. Department of Veterans Affairs, 2018a). The military conflicts of the Post 9/11 era, such as Operation Iraqi Freedom and Operation Enduring Freedom, increased combat operations and subsequently grew the size of the military, resulting in the largest surge of reintegrating veterans in recent history. The transition from active duty to veteran status often requires service members to move from certainty, routine, commu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 11 publications
1
3
0
Order By: Relevance
“…Three veterans explicitly discussed the role of their dog in reducing suicidality. This is consistent with previous qualitative studies that have reported the role of an assistance dog as a protective factor for suicidality [ 25 , 26 ]. Interestingly, participants in our study did not raise concerns regarding experiencing challenges, such as managing their dog’s needs and feeling overwhelmed when in public spaces due to the attention they received when they went out with their dog, as was found in a previous study [ 27 ].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Three veterans explicitly discussed the role of their dog in reducing suicidality. This is consistent with previous qualitative studies that have reported the role of an assistance dog as a protective factor for suicidality [ 25 , 26 ]. Interestingly, participants in our study did not raise concerns regarding experiencing challenges, such as managing their dog’s needs and feeling overwhelmed when in public spaces due to the attention they received when they went out with their dog, as was found in a previous study [ 27 ].…”
Section: Discussionsupporting
confidence: 93%
“…Qualitative studies frequently reported reductions in suicidality, with veterans accrediting their assistance dog with keeping them alive [ 24 , 25 , 26 , 27 ]. McLaughlin and Hamilton (2019) explored the influence of service dogs on participation in daily occupations in Australian veterans with PTSD [ 26 ].…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, a systematic review that included military personnel, where the main exposure was a concussion or mild traumatic brain injury, identified that these conditions confer a twofold increased risk of suicide [ 8 ]. However, a series of protective factors against suicide risk have also been studied, such as programs that facilitate assistance to the military, assistance with social networks, family support and educational counseling sessions, factors that are little evaluated [ 9 ]. Thus, it is critical to evaluate this group.…”
Section: Introductionmentioning
confidence: 99%
“…Our previous engagement projects confirmed that many veterans are unfamiliar with the research process and are uncomfortable embracing the role of research partner. Operation PCOR was designed based on veterans' expressed concerns and recommendations elicited from our previous engagement projects (Flynn et al, 2019;Krause-Parello, et al, 2019). Therefore, the overarching goal of this current project was two-fold: 1.…”
Section: Rationale Informing the Projectmentioning
confidence: 99%